1996
DOI: 10.2514/3.13398
|View full text |Cite
|
Sign up to set email alerts
|

Controlled leading-edge suction for management of unsteady separation over pitching airfoils

Abstract: The effect on the unsteady surface pressures of controlled suction from a span wise slot, located at 2% chord in the suction surface of a two-dimensional NACA 0012 airfoil model, was examined in detail for a wide range of pitch rates with a constant velocity ramp motion. The experiments were conducted in the Andrew Fejer Wind 1\mnel at the Illinois Institute of Technology's Fluid Dynamics Research Center. The optimum suction required to meet three different control objectives, suppression of the dynamic-stall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…A low reduced frequency may cause the disappearance of LEV, resulting in the lack of a sudden increase of C L . An even lower reduced frequency could eliminate the dynamic stall features completely and make the flow quasi-steady, which was also verified by the experimental study of Alrefai and Acharya [6]. However, Lee and Gerontakos [7] found in their experiments that the reduced frequency had little impact on the location and size of LEV.…”
Section: Introductionmentioning
confidence: 70%
“…A low reduced frequency may cause the disappearance of LEV, resulting in the lack of a sudden increase of C L . An even lower reduced frequency could eliminate the dynamic stall features completely and make the flow quasi-steady, which was also verified by the experimental study of Alrefai and Acharya [6]. However, Lee and Gerontakos [7] found in their experiments that the reduced frequency had little impact on the location and size of LEV.…”
Section: Introductionmentioning
confidence: 70%
“…Control of dynamic stall and its distinctive vortex has consequently been investigated using passive methods such as vortex generators [11] and slats [12] as well as active blowing [13], suction [7,14] and buzzing [15] methods with the aim of maintaining beneficial lift increases while decreasing drag and pitching moment. While these studies have shown some success, flow control using synthetic jets [16][17][18][19] has shown great potential for managing dynamic stall aerodynamic coefficient excursions due to their actuation versatility [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that shedding the unsteady vorticity from some downstream location in smaller chunks of uid can provide an acceptable solution to prevent the vortex from forming. Then the drastic consequences of the vortex-induced pitching moment variations can be avoided, even if the ow separates partially.As the equationindicates,using either surfaceacceleration 3 or surface mass transfer such as blowing and/or suction 6 enables some degree of vorticity ux manipulation. The latter has been a popular approach to control of steady ows, but has only been partly satisfactory in dynamic stall control for incompressible conditions.…”
Section: Nomenclaturementioning
confidence: 99%